A C∧S-Cyclometallated Gold(III) Complex as a Novel Antibacterial Candidate Against Drug-Resistant Bacteria - Ratia, Carlos; Cepas, Virginio; Soengas, Raquel; Navarro, Yolanda; Velasco-de Andrés, María; Iglesias, María José; Lozano, Francisco; López-Ortiz, Fernando; Soto, Sara M. (Frontiers in Microbiology, 2022)
The worldwide emergence and spread of infections caused by multidrug-resistant bacteria endangers the efficacy of current antibiotics in the clinical setting. The lack of new antibiotics in the pipeline points to the need of developing new strategies. Recently, gold-based drugs are being repurposed for antibacterial applications. Among them, gold(III) complexes have received increasing attention as metal-based anticancer agents. However, reports on their antibacterial activity are scarce due to stability issues. The present work demonstrates the antibacterial activity of the gold(III) complex 2 stabilized as C˄S-cycloaurated containing a diphenylphosphinothioic amide moiety, showing MIC values ranged from 4 to 8 mg/L and from 16 to 32 mg/L among Gram-positive and Gram-negative MDR pathogens, respectively. Complex 2 has a biofilm inhibitory activity only 2 to 4 times than its MIC. We also describe for the first time a potent antibacterial synergistic effect of a gold(III) complex combined with colistin, showing a bactericidal effect in less than two hours; confirming the role of the outer membrane as a permeability barrier. Complex 2 shows a low rate of internalization in Staphylococcus aureus and Acinetobacter baumannii, it does not interact with replication enzymes or efflux pumps, causes ultrastructural damages in both membrane and cytoplasmic levels and permeabilizes the bacterial membrane. Unlike control antibiotics, complex 2 did not generate resistant mutants in 30-day sequential cultures. We detected lower cytotoxicity in a non-tumoral THLE-2 cell line (IC50=25.5 µM) and no acute toxicity signs in vivo after an i.v. 1 mg/Kg dose. The characterization presented here reassures the potential of complex 2 as a new chemical class of antimicrobial agents.